Endoscopic assisted resection of base of tongue lesion: a case report - Pillai D., Aishwarya Raj; Prasad, Kothegala C.; Pilakkilakkandiyil, Anjali; Gopinath, Indu V.; Subramani, Brindha H.; Gowda, Harshitha N.; Gupta, Arjun (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Surgery for the base of the tongue lesions can be challenging since this area is difficult to access and contains important neurovascular structures. External incision in the neck via an approach that varies from a transoral midline glossotomy approach to a lip-split mandibulotomy, which inevitably results in obvious scarring of the face and neck. Transoral robotic surgery can be considered for removal of these difficult neoplasms. But limitations of robotic surgery include the size and cost of the device, a learning curve, and safety concerns. Hence, alternative surgical approaches that allow for good exposure, complete tumour excision, low complication rates, low recurrence rates, and no postoperative neck scarring are preferred.